Moral neutrality as legal value: critical analysis of philosophical and legal arguments of A. V. Nekhaev - A. B. Didikin (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the analysis of the arguments expressed by A. V. Nekhaev in his paper with the criticism of the positivist model of law proposed by H. Hart and J. Raz. On the basis of modern trends and discussions in the analytical philosophy of law the author shows the groundlessness of the proposed hypothetical division into «calorie» and «dietary» theories in the question of the distinction between law and morality. It is noted that the classification should take into account the flexibility of positivist argumentation and the impossibility of accurate identification of philosophical and legal theories in modern conditions. The author concludes that moral neutrality in the application of legal norms is a legal value that contributes to the rule of law in theoretical discussions and in practice